More integration or more disintegration in the European Union? A sociological perspective - Hadzhidimova, Lora (Politikon: The IAPSS Journal of Political Science, 2019)
This paper analyzes the scholarly debate about integration in the European Union; its emergence, evolution and current state. It examines works employing theoretical and problem-driven approaches, dedicated to analyzing integration as their main object. The findings suggest that the debate has progressed significantly - a fact evident by the change of the initial question with which scholars engaged – whether international organizations and institutions have a future as independent entities. The way the EU integration was explored has also gradually shifted from paradigmatic debates, mostly between realists and liberalists, to diverse problem-driven contributions. This new, pragmatic approach is preferred as an effort to better explain the complex question of the EU integration in times of crises. An assessment of this debate is required to improve the quality of the future research agendas, methodological approaches, and policy recommendations of the field.